Analisa Tingkat Kepuasan Penumpang Terhadap Pelayanan Kereta Api Kelas Eksekutif Bima di Stasiun Gubeng Pada Saat Penerapan New Normal - Aulia Syavila; Nugroho Utomo (Universitas Dr. Soetomo, 2023)
The entry of the Covid-19 virus in early 2020 in Indonesia has changed the order of people's lives. One of the sectors affected by the Covid-19 outbreak is rail transportation. The existence of the Covid-19 virus has resulted in a decrease in the number of train passengers at Gubeng Station. One of the trains that is ready to be operated again by implementing the Covid-19 prevention protocol in the implementation of the New Normal is the Bima Executive Train. Bima Executive Train is an executive class train with a relation of Surabaya Gubeng Station - Gambir Station. In this study, an analysis will be carried out using the Importance Performance Analysis (IPA) method. This research is a type of descriptive-quantitative research. The population of this study was passengers who used the services of the Bima Executive Train at Gubeng Station. Based on the results of data processing and analysis, the value of the level of conformity between the performance value and expectations at the time of the implementation of the New Normal at Gubeng Station and at the Bima Executive Train was as follows: at Gubeng Station, the largest level of conformity value was 97.56%, namely speed and accuracy in the train departure schedule. Meanwhile, in the Bima Executive Railway, the largest level of conformity value is 98.19%, namely the accuracy of officers in providing information related to train travel disturbances. The average value of the service attributes that describe the level of passenger satisfaction at Gubeng Station, in general reflects the level of satisfaction or excellent quality of service. This is evident from the 25 service attributes that have a value of 4.09, namely